The oldest record of aquatic amniote congenital scoliosis - Szczygielski, Tomasz; Surmik, Dawid; Kapuścińska, Agnieszka; Rothschild, Bruce M. (PLOS ONE, 2017)
We report the first occurrence of congenital scoliosis in an early Permian aquatic parareptile, Stereosternum tumidum from Paraná state, Brazil. The spine malformation is caused by a congenital hemivertebra. These observations give insight into the biomechanical aspects of underwater locomotion in an axial skeleton-compromised aquatic amniote. This is the oldest record of a hemivertebra in an aquatic animal.